2005
DOI: 10.1056/nejmoa044241
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Single Infusion of Zoledronic Acid with Risedronate for Paget's Disease

Abstract: A single infusion of zoledronic acid produces more rapid, more complete, and more sustained responses in Paget's disease than does daily treatment with risedronate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
231
2
21

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(260 citation statements)
references
References 22 publications
6
231
2
21
Order By: Relevance
“…The magnitude of remodeling suppression has been shown to differ in several separate head-to-head studies using serum and urine biomarkers [8][9][10]. These studies consistently show alendronate suppresses remodeling more than risedronate [8,9] while zoledronate suppresses more than risedronate [10].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of remodeling suppression has been shown to differ in several separate head-to-head studies using serum and urine biomarkers [8][9][10]. These studies consistently show alendronate suppresses remodeling more than risedronate [8,9] while zoledronate suppresses more than risedronate [10].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The magnitude of remodeling suppression has been shown to differ in several separate head-to-head studies using serum and urine biomarkers [8][9][10]. These studies consistently show alendronate suppresses remodeling more than risedronate [8,9] while zoledronate suppresses more than risedronate [10]. No head-tohead assessments of bone remodeling among the BPs has been conducted using histology as an outcome, yet based on iliac crest biopsy studies from the major clinical trials the percent suppression of remodeling relative to placebo-treated controls tends to be quite similar over 3 years with daily risedronate (-40%) [11], daily alendronate (-92%) [12], intermittent oral ibandronate (-50%) [13], and zoledronate (-63%) [14].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…91 For many years pamidronate given by intravenous infusion was used extensively, 92 but the newer and more potent bisphosphonates can produce even more profound suppression of disease activity than was possible with the bisphosphonates available in previous years. 93,94 The latest advance is with zoledronate, 95 which, when given as a single 5-mg infusion, produced a greater and longerlasting suppression of excess bone turnover than even oral risedronate given at 30 mg/day over 2 months, hitherto one of the most effective treatments.…”
Section: Clinical Applications Of Bisphosphonatesmentioning
confidence: 99%
“…Extending this further, the effects of once-yearly zoledronic acid on BMD and bone turnover were found to be equivalent to an every-3-month regimen [75]. A recent study demonstrated that a single Guise 1129 www.TheOncologist.com injection of zoledronic acid was superior to daily treatment with risedronate for Paget's disease, characterized by high bone turnover [76]. Ongoing trials are evaluating whether this yearly dosing regimen can also reduce fracture risk in patients with osteoporosis.…”
Section: Alternate Bisphosphonate Dosing Regimensmentioning
confidence: 99%